Polarimetric Differential Imaging with Vlt/Naco - Perez-Marquez, S (EDP Sciences, 2024)
Context. The observed diversity of exoplanets can possibly be traced back to the planet formation processes. Planet–disk interactions induce sub-structures in the circumstellar disk that can be revealed via scattered light observations. However, a high-contrast imaging technique such as polarimetric differential imaging (PDI) must first be applied to suppress the stellar diffraction halo. Aims. In this work we present the PDI PiPelIne for NACO data (PIPPIN), which reduces the archival polarimetric observations made with the NACO instrument at the Very Large Telescope. Prior to this work, such a comprehensive pipeline to reduce polarimetric NACO data did not exist. We identify a total of 243 datasets of 57 potentially young stellar objects observed before NACO’s decommissioning. Methods. The PIPPIN pipeline applies various levels of instrumental polarisation correction and is capable of reducing multiple observing setups, including half-wave plate or de-rotator usage and wire-grid observations. A novel template-matching method is applied to assess the detection significance of polarised signals in the reduced data. Results. In 22 of the 57 observed targets, we detect polarised light resulting from a scattering of circumstellar dust. The detections exhibit a collection of known sub-structures, including rings, gaps, spirals, shadows, and in- or outflows of material. Since NACO was equipped with a near-infrared wavefront sensor, it made unique polarimetric observations of a number of embedded protostars. This is the first time detections of the Class I objects Elia 2-21 and YLW 16A have been published. Alongside the outlined PIPPIN pipeline, we publish an archive of the reduced data products, thereby improving the accessibility of these data for future studies. © 2024 EDP Sciences. All rights reserved.